(untitled) (Advancements in Homeopathic Research, 2025)
Background: Typically, the human body has the yeast Candida albicans, which is mostly located in the gut, vagina, throat, and mouth. It is the most prevalent fungal infection in humans. Seventy-five percent of women have had vaginal candidiasis at least once a lifetime and 5-8% of them relapse while they are at their most fertile. Immunocompromised individuals, denture wearers, and young children are all susceptible to oral candidiasis. Because of the emergence of drug resistance, new antifungal medications are required for the effective treatment of Candida albicans infection. Objective: The current study’s objectives are to reduce issues, encourage an early recovery, provide specific homoeopathic treatment with symptomatic improvement, support utilize homoeopathy in the management and prevention of fungal maladies, and assess the efficacy of homoeopathic medications in suppressing Candida albicans. An overview of the pathogenicity traits, clinical manifestations, and participation of Candida albicans in invasive infections is provided by the review. Method: A variety of automated database literature searches were performed in order to gather and condense pertinent articles. These searches included Research Gate, PubMed and Google Scholar. Result: Homoeopathy on Candida albicans have been shown to have possibilities for novel and dependable techniques for inhibiting fungal infections. Interpretation: This review discusses the methods and the remedies to inhibit Candida albicans & the significance of homoeopathic medicine’s antifungal properties